Root system size and root hair length are key phenes for nitrate acquisition and biomass production across natural variation in Arabidopsis. (19th March 2022) - De Pessemier, Jérôme; Moturu, Taraka Ramji; Nacry, Philippe; Ebert, Rebecca; De Gernier, Hugues; Tillard, Pascal; Swarup, Kamal; Wells, Darren M; Haseloff, Jim; Murray, Seth C; Bennett, Malcolm J; Inzé, Dirk; et al.
Abstract : A positive correlation was found between root system size and high-affinity nitrate uptake in a core set of Arabidopsis natural accessions, emphasizing the benefits of an exploratory root organ in plant nitrogen acquisition. Abstract: The role of root phenes in nitrogen (N) acquisition and biomass production was evaluated in 10 contrasting natural accessions of Arabidopsis thaliana L. Seedlings were grown on vertical agar plates with two different nitrate supplies. The low N treatment increased the root to shoot biomass ratio and promoted the proliferation of lateral roots and root hairs. The cost of a larger root system did not impact shoot biomass. Greater biomass production could be achieved through increased root length or through specific root hair characteristics. A greater number of root hairs may provide a low-resistance pathway under elevated N conditions, while root hair length may enhance root zone exploration under low N conditions. The variability of N uptake and the expression levels of genes encoding nitrate transporters were measured. A positive correlation was found between root system size and high-affinity nitrate uptake, emphasizing the benefits of an exploratory root organ in N acquisition. The expression levels of NRT1.2 / NPF4.6, NRT2.2, and NRT1.5 / NPF7.3 negatively correlated with some root morphological traits. Such basic knowledge in Arabidopsis demonstrates the importance of root phenes to improve N acquisition and paves the way to design eudicot ideotypes.